2017
DOI: 10.1002/lary.26834
|View full text |Cite
|
Sign up to set email alerts
|

Constructing a patient‐specific computer model of the upper airway in sleep apnea patients

Abstract: Objective: The use of computer simulation to develop a high-fidelity model has been proposed as a novel and costeffective alternative to help guide therapeutic intervention in sleep apnea surgery. We describe a computer model based on patient-specific anatomy of obstructive sleep apnea (OSA) subjects wherein the percentage and sites of upper airway collapse are compared to findings on drug-induced sleep endoscopy (DISE).Study Design: Basic science computer model generation.Methods: Three-dimensional finite ele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 34 publications
0
12
0
1
Order By: Relevance
“…The first focused on the microgravity [ 41 ], while the second one targeted on Down syndrome [ 42 ]. A Google Scholar search for grey literature yielded four results, totaling 27 studies conclusive for qualitative synthesis in this review [ 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 ].…”
Section: Study Selectionmentioning
confidence: 99%
See 3 more Smart Citations
“…The first focused on the microgravity [ 41 ], while the second one targeted on Down syndrome [ 42 ]. A Google Scholar search for grey literature yielded four results, totaling 27 studies conclusive for qualitative synthesis in this review [ 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 ].…”
Section: Study Selectionmentioning
confidence: 99%
“…Ilegbusi et al [ 56 ] discovered that a supine position without dilator muscle activation decreased airway cross-sectional width at the tongue, epiglottis, and larynx levels. Dhaliwal et al [ 52 ] reported that different patients had different sites of maximal collapse, including the soft palate, tongue base, and oropharynx. Moreover, the cross-sectional area of the airway was often illustrated with the displacement and deformation of the soft palate.…”
Section: Thematic Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…This study describes a computer model based on patient-specific anatomy in those with OSA wherein the percentage and sites of UA collapse are compared with findings with DISE. 309 Three-dimensional finite element techniques were undertaken for model development in a pilot study of 4 individuals with OSA. Magnetic resonance imaging was used to capture images of patients' anatomy, and a software program was used to outline critical anatomical structures.…”
Section: Pathophysiology and Medical Implicationsmentioning
confidence: 99%